The time-course of cyclic AMP signaling is critical for leukemia U-937 cell differentiation - Shayo, Carina Claudia (2004)
The regulation of the cAMP signaling is intimately involved in several cellular processes, including cell differentiation. Here, we provide strong evidence supporting that the time-course of cAMP signal is critical for leukemia U-937 cell differentiation. Three stimulating-cAMP agents were used to analyze the correlation between cAMP time-course and cell differentiation. All three agents denoted similar cAMP maximal responses in dose-response experiments. The kinetic of desensitization showed differential characteristics, while H2 receptor desensitized homologously without affecting PGE2 or forskolin effect, PGE2 response showed mixed desensitization characterized by a homologous initial phase followed by a heterologous phase. Regarding forskolin, long-term stimuli attenuated PGE2 and H2 agonist response without affecting adenylyl cyclase activity. In the absence of phosphodiesterase inhibitors, the three agents induced similar maximal cAMP levels after 5 min, but only that induced by the H2 agonist returned to basal levels. Consistent with this observation, H2 agonist was not able to induce U-937 cell maturation in contrast to PGE2 and forskolin, supporting the importance of time-course signaling in the determination of cell behavior.